Predictors of resectability in breast-conserving therapy - Rath, Michèlle Geneviève; Heil, Jörg; Domschke, Christoph; Sinn, Peter; Marmé, Frederik; Scharf, Alexander; Schneeweiss, Andreas; Sohn, Christof; Rom, Joachim (Archives of gynecology and obstetrics, 2012)
BackgroundOur goal is to identify subgroups of women undergoing breast-conserving therapy (BCT) who are at increased risk for requiring a secondary surgical procedure, and to identify tumor and patient profiles that will allow surgeons to anticipate the need for taking larger margins when removing the tumor.MethodsOne hundred female patients who had palpable, invasive carcinomas of the breast, and had undergone a primary BCT, were included in the study. Of these, all women (n = 25) who had incomplete resections, or questionable margins of resection, had to undergo re-excisions.ResultsPatients who had multifocal disease, accompanying ductal carcinoma in situ, involvement of regional lymph nodes, high-grade breast cancer (Grade 3 vs. 1/2), lympho-vascular invasion or negative hormone-receptor-status, were significantly more likely to have undergone incomplete removal of tumor tissue—these patients thus required a secondary surgery.ConclusionThe clinical and pathological predictors described above indicate that surgery in breast cancer patients meeting these criteria require larger safety margins to minimize the incidence rate of re-excision at a later date.
Gesehen am 06.04.2018